Literature anxiety among Malaysian secondary school students. - Liau, Agnes Wei Lin
The detrimental effects of anxiety on academic performance has been an area of concern for many language educators. In Malaysia, the inclusion of the literature programme in the English Language subject aimed to improve students' proficiency in the English language and also to introduce and acquaint the students with other world-views and cultures.